(untitled) (Journal of Advances and Scholarly Researches in Allied Education, 2022)
The social structure and the culture of society have great influence on the functioning of Cultural Environment activities. Each society has its own culture which consists of the customs, values, attitudes, beliefs, habits, languages and other forms of interaction between the members of the society. Any business firm which aims at entering any market for its products and services must develop complete understanding of socio economic philosophy of the society. In the era of globalisation, no business can survive and grow without social harmony and without understanding the impact of demographic changes in the country or in a region. This paper focuses on the changes in socio-economic environment in India and its impact on Indian Region in the future. The population realized these changes and took steps to reduce their fertility but the decline in fertility was not so steep. As a result the global population has undergone a fourfold increase in a hundred years and has reached in billions. This study will enlighten the changing pattern of population growth and planning in Indian Region.